2006
DOI: 10.1007/s10461-005-9051-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Expressive Writing on Adjustment to HIV

Abstract: Previous research suggests that writing about stressful experiences results in better health and psychological well-being. In the present study, a multi-ethnic sample of 79 HIV-positive women and men participated in a structured interview, and wrote about either their deepest thoughts and feelings about living with HIV (expressive writing) or their activities in the last 24 hr (control). Sixty-two participants returned for the 2-month follow-up and 50 returned for the 6-month follow-up interview. Oral fluid sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 53 publications
4
35
2
1
Order By: Relevance
“…This is not in line with an earlier study in which promising results for the effects of structured writing were found for people with HIV [22,23]. Future studies should examine individual differences and the influence of increasing the frequency of sessions.…”
Section: Discussioncontrasting
confidence: 93%
“…This is not in line with an earlier study in which promising results for the effects of structured writing were found for people with HIV [22,23]. Future studies should examine individual differences and the influence of increasing the frequency of sessions.…”
Section: Discussioncontrasting
confidence: 93%
“…These hypotheses were in line with findings from prior research (e.g. Pennebaker, 1993;Pennebaker, Mayne & Francis, 1997;Rivkin et al, 2006).…”
supporting
confidence: 91%
“…In addition, several other studies (e.g. Park & Blumberg, 2002;Rivkin, Gustafson, Weingarten & Chin, 2006;Slavin-Spenny, Cohen, Oberleitner & Lumley, 2011) have found no effect of expressive writing on stressrelated growth. Frattaroli's (2006) meta-analysis also demonstrated that there is currently insufficient evidence to conclude that expressive writing can facilitate posttraumatic growth, but that methodological differences may have influenced existing study outcomes.…”
mentioning
confidence: 86%
“…An initial improvement in viral load was observed between preand postintervention; however, no subsequent improvement was seen across the 6 month follow-up time frame. Rivkin et al (2006) found no difference between the expressive writing and the control writing groups on depressive symptoms, immune function, or perceived positive and negative changes related to HIV diagnosis. A study by Marston (2003) also found no main effects for an expressive writing group when compared to a control group, but did find that individuals low on avoidance in the expressive writing group had lower negative mood at the 2 month follow-up when compared with those individuals who were high on avoidance.…”
Section: Introductionmentioning
confidence: 61%